Pleasures of Benthamism : Victorian literature, utility, political economy - Blake, Kathleen (Oxford : Oxford University Press, 2009)
A fresh look at the often-censured but imperfectly understood traditions of Utilitarianism and political economy in relation to Victorian literature and culture.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Bentham, Jeremy, -- 1748-1832.; English literature -- 19th century -- History and criticism; Utilitarianism; Economics and literature -- Great Britain -- History -- 19th century